CORRELATION OF SCHOOL LITERATION WITH THE RESULTS OF LEARNING ON MATHEMATIC IN THE SITUSARI 01 ELEMENTARY SCHOOL - Nurlinda Safitri; Lia Octaviani (UNIVERSITAS PAKUAN, 2018)
This research is about the correlation study with the school literacy as independent variable and result of learning mathematics as dependent variable. The main purposes of the research is for find out relation between school literacy with result of learning mathematics. The research implemented at March 2018 and use survey research with correlational approachment. The subject on the research are students four grade in the Situsari 01 Elementary School with 101 students. Sampling from formula calculation is 50 student using Taro Yamane formula with 10%. The technique of data analysis are regretion technique analysis and simple correlation. Regretion technique analysis and simple correlation produce a relation model otherwise in type equation Ŷ = -22,12 + 0,86x, with Fhitung is 48 bigger than Ftabel with the real level 0,05 with 4,04, and be based on contribution the outcomes of research is 94%, so can summed up that there is a positive and significant relation between school literacy with result of learning mathematics.